MODEL PENTAHELIX DALAM PENGEMBANGAN PARIWISATA DI DESA WISATA LIYANGAN KABUPATEN TEMANGGUNG YANG TERINTEGRASI DAN BERKELANJUTAN - Setyawan, Bagus; Yuniningsih, Tri; Hongwiset, Sunee (Institut Riset dan Pengembangan Indonesia, 2025)
This article aims to analyze the integrated and sustainable development of tourism in Liyangan Tourism Village, analyze the supporting factors in the integrated and sustainable development of tourism in Liyangan Tourism Village, and describe the helix model in the integrated and sustainable development of tourism in Liyangan Tourism Village. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documents on tourism development in Liyangan Tourism Village. The results of the study indicate that tourism development in Liyangan Tourism Village, Temanggung Regency is integrated and sustainable because most aspects such as geographical proximity, tourist attractions, supporting facilities, institutional elements, directors, social and cultural, and the environment are integrated and sustainable. However, accessibility and the economy are not yet integrated and sustainable. Supporting factors in tourism development in Liyangan Tourism Village include values, communication, trust, and policies. The helix model in integrated and sustainable tourism development in Liyangan Tourism Village is generally optimal through strong collaboration between the government, academics, and the community. However, the business sector and mass media are still not optimal due to limited capacity and inconsistent promotion, this indicates the need for greater involvement to achieve full integration and sustainability.